Urologic cancer in Thailand - Bannakij Lojanapiwat (2018)
© The Author 2015. Published by Oxford University Press. All rights reserved. Cancer is a major health burden among non-communicable diseases, which has had a high impact on the healthcare system in Thailand. Based on GLOBOCAN, the prevalence of urologic cancer is increasing in Thailand. Prostate, bladder and kidney cancers are 6th, 15th and 22nd most common cancers, respectively, in both males and females. Prostate cancer is the fourth most common cancer in male. Cancer in the lower socioeconomic groups is a challenging problem due to greater exposure to the risk factors and more limited access to the healthcare service. The cancers are usually detected in advanced stages of the cancer. The most common histopathological finding of kidney cancer is a renal cell carcinoma. Transitional cell carcinoma is the most common histopathology of bladder. There is a trend of stage migration to earlier stages at first presentation, probably due to public awareness and laboratory screening. Patients with early stage are treated with minimally invasive modalities such as endoscopic, laparoscopic or robot-assisted laparoscopic surgery. Laparoscopic radical prostatectomy and robot-assisted laparoscopic radical prostatectomy is the mainstay treatment of localized prostate cancer with the better outcome and less complication. Androgen deprivation therapy is usually for elderly or unfit patients. The strategy for early detection of early cancer is the important role of Thai urologists to manage these three common urologic cancers.